2021
DOI: 10.1111/conl.12832
|View full text |Cite
|
Sign up to set email alerts
|

Mischaracterizing wildlife trade and its impacts may mislead policy processes

Abstract: Overexploitation is a key driver of biodiversity loss but the relationship between the use and trade of species and conservation outcomes is not always straightforward. Accurately characterizing wildlife trade and understanding the impact it has on wildlife populations are therefore critical to evaluating the potential threat trade poses to species and informing local to international policy responses. However, a review of recent research that uses wildlife and trade-related databases to investigate these topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 55 publications
0
50
0
Order By: Relevance
“…For example, recent wildlife market surveys conducted in countries where international and domestic trade coexist have shown that both CITES regulations and harvest and trade quotas are often violated, and that disentangling legal and illegal trade is a difficult task [6]. It is of great concern that mischaracterization of legal and illegal wildlife trade and its impacts on the conservation of traded species can mislead policy processes [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent wildlife market surveys conducted in countries where international and domestic trade coexist have shown that both CITES regulations and harvest and trade quotas are often violated, and that disentangling legal and illegal trade is a difficult task [6]. It is of great concern that mischaracterization of legal and illegal wildlife trade and its impacts on the conservation of traded species can mislead policy processes [7].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the trade analyses and conclusions presented by Khanwilkar et al (2022) should be interpreted as an unreliable, and most likely, serious mischaracterization that overstates actual tiger import levels in the United States. USFWS LEMIS data misconceptions and errors are common among wildlife trade studies that have not received peerreview from LEMIS data experts (Challender et al, 2022); Khanwilkar et al (2022) appears to fall into this category. Unless LEMIS data are verified and interpreted correctly, results of their analyses may mischaracterize and overstate trade and risk misinforming policy processes related to the conservation impacts of tiger farming, ultimately to the detriment of wildlife conservation.…”
mentioning
confidence: 99%
“…One of our major criticisms of Frank and Wilcove (2019) was that their recommendations were poorly developed, overlooking critical factors that would impede real-world adoption (Challender et al, 2021). There is far more exposition and "nuance" in their response to our commentary than their original article.…”
mentioning
confidence: 93%
“…It is difficult to reconcile this title and statements within the article with the assertion that Harrington et al did not conclude that the pet trade posed a threat to wild populations of Asian otters.However, our primary concern is that Harrington et al's analysis of trends in popularity of social media videos of pet otters makes the jump to strongly endorsing an international trade policy (specifically, including two otter species in CITES Appendix I) despite the authors acknowledging that there is no evidence of a link between social media trends and trade trends. Trade bans via CITES may be considered as a sensible precautionary measure by some, but in some instances, they may do more harm than good for species (Challender et al, 2021). To avoid this scenario, the risks and benefits of such proposals should be fully assessed (Cooney et al, 2021).Regarding CITES source code "I," users of data with this source code should be aware that CITES Parties use this code in various ways and therefore be clear whether data refer to illegal trade or legal (re-)exports of previously seized specimens.…”
mentioning
confidence: 99%
See 1 more Smart Citation